Fibrous coproducts of corn and citrus for dairy cows - Silva, Wesley de Rezende (2021)
The objective of this experiment was to evaluate four strategies of feeding fibrous coproducts to lactating dairy cows. Twenty Holstein cows (180 ± 51 days in lactation, 8 primiparous) in five 4 × 4 Latin squares (21-day periods) were fed a combination of two feeding strategies in a 2 x 2 factorial arrangement of treatments. Strategies were: 1) Concentrate feeds: the partial replacement of wet corn gluten feed (GF) by an iso-N blend of pelleted citrus pulp plus corn distillers dried grains (CD). 2) Forage feeds: the partial replacement of whole plant corn silage (CS) by corn ear fibrous coproduct (CO) dry matter (DM). The goal was to have diets with 20 and 5% of DM of both GF and CO and to have a 50% replacement of CS by CO. The calculated concentration of physically efective neutral detergent fiber (peNDF>8) was reduced from 21.8% of DM on CS to 19.2% of DM on CO and peNDF>8 was 20.7% of DM on GF and 20.2% of DM on CD. Dietary starch ranged from 21.0 to 23.5% of DM. Statistical significance was declared at P ≤ 0.05 and trends at 0.05 < P ≤ 0.10. The CS-CD diet had the highest yield of 4% fat corrected milk (28.5 kg/d) and energy corrected milk (30.0 kg/d) relative to the other diets. Milk fat content was reduced on CO relative to CS. Cows fed the CO diets had higher DM intake (DMI) (21.2 vs. 20.2 kg/d) and lower feed efficiency than CS. Diets CO reduced the intake of peNDF>8 (kg/d) and the intake of peNDF>8, forage NDF, and total NDF as % of body weight relative to CS. Diets CO reduced the mean meal duration, the duration of the largest daily meal, and rumination and eating behaviors (min/d and min/kg of DMI). The total tract starch digestibility was lower on CO than CS but the intake of digestible starch was higher on CO than CS. Diet CO-GF had the lowest NDF digestibility. The GF reduced milk yield (29.6 vs. 30.8 kg/d), tended to reduce DMI (20.4 vs. 21.0 kg/d), and reduced the intake of digestible organic matter. The type of concentrate did not affect the intake of peNDF>8 and feed efficiency. Meal frequency was increased and mean meal duration and the duration and size of the largest daily meal were reduced by GF. The GF increased rumination (min/d, min/kg of DMI, and min/kg of peNDF>8). The intake of digestible starch tended to be increased by GF. Rumen microbial yield did not differ. The regulation of feed intake by long NDF ocurred in a theoretically low forage diet in response to change in roughage source and the intake of digestible starch was apparently involved on intake regulation and chewing behavior when the nature of concentrates was altered at constant roughage in the diet. All nutritional strategies evaluated were nutritionaly viable, although there was a trend for income over cost to be higher on CS than CO and type of concentrate had no effect on return per cow.